2019
DOI: 10.1097/mat.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Hybrid Mock Circulation for Hydraulic Investigations of Active and Passive Cardiovascular Implants

Abstract: During the development process of active or passive cardiovascular implants, such as ventricular assist devices or vascular grafts, extensive in vitro testing is required. The aim of the study was to develop a versatile hybrid mock circulation (HMC) that can support the development of such implants that have a complex interaction with the circulation. The HMC operates based on the hardware-in-the-loop concept with a hydraulic interface of four pressure-controlled reservoirs allowing the interaction of the impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…This loop relied on the inherent compliance of trapped air but is limited in recreating high frequency and physiologic waveforms. 19 Petrou et al 20 reported their versatile hybrid mock circulation loop, which can model three different conditions: a BiVAD, a TAH, and the flow distribution of a total cavopulmonary connection (TCPC) in a Fontan circulation. These authors examined the loop performance of complex active or passive cardiovascular implants, such as TAHs and TCPCs, and found it difficult to validate the numerical models used with clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…This loop relied on the inherent compliance of trapped air but is limited in recreating high frequency and physiologic waveforms. 19 Petrou et al 20 reported their versatile hybrid mock circulation loop, which can model three different conditions: a BiVAD, a TAH, and the flow distribution of a total cavopulmonary connection (TCPC) in a Fontan circulation. These authors examined the loop performance of complex active or passive cardiovascular implants, such as TAHs and TCPCs, and found it difficult to validate the numerical models used with clinical observations.…”
Section: Discussionmentioning
confidence: 99%
“…C, In vitro setup. The pVAD is connected to the actuation system and two tanks of the hybrid mock circulation (HMC) 25 that dynamically apply the pressure in the pump chamber, the left ventricular (LVP) and aortic (AoP) pressures at the pVAD inlet and outlet, respectively. The pressure is measured at the pump inlet and outlet, providing information regarding left ventricular and aortic pressure.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro experiments were conducted on a hybrid mock circulation (HMC) system described earlier by Petrou et al 25 On this HMC, the CVS is simulated only numerically and in real time. The computed values were applied via a hydraulic interface to two pressure-controlled reservoirs that represented the left ventricle and the aorta ( Figure 1C), respectively.…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…The in vitro tests were conducted on the testbench described earlier by Petrou et al with only the left side being connected to the pVAD. Figure shows the recorded metrics and their respective measurement location.…”
Section: Methodsmentioning
confidence: 99%